Unraveling the spatiotemporal dynamics and drivers of surface and tropospheric ozone in China - Shuai Yin; Chong Shi; Husi Letu; Zhijun Jin; Qingnan Chu; Huazhe Shang; Dabin Ji; Meng Guo; Kunpeng Yi; Xin Zhao; Tangzhe Nie; Zhongyi Sun (Environment International)
In China, the rapid development of the economy and the implementation of multiple mitigation strategies in recent decades have led to dramatic changes in air quality. In this study, ground- and satellite-based observations were integrated to comprehensively investigate the spatiotemporal variations of nationwide surface-level and tropospheric ozone (O3). Additionally, a meteorology correction model was developed, combining decomposition analysis and stepwise multiple linear regression, to explore the influence of meteorological conditions, anthropogenic emissions, and control actions on surface and tropospheric O3 in China. The results suggest that O3 pollution in China has strong spatial characteristics and seasonal patterns. The nationwide tropospheric O3 pollution substantially deteriorated from 2005 to 2020, and the increasing rate of tropospheric column O3 in the four target regions ranged from 0.20 (0.15–0.26) Dobson Units yr−1 to 0.26 (0.17–0.34) Dobson Units yr−1. Simultaneously, the meteorological factors exerted distinct influences on the surface-level and tropospheric O3 by regions. Since 2018, both surface and tropospheric O3 have declined remarkably in China. The meteorology correction model indicates that the downward trend is primarily attributed to the implementation of effective control plans (the Three-Year Action Plan for Cleaner Air) and the reduction of anthropogenic emissions. However, it is notable that surface-level O3 in autumn–winter, particularly in the eastern and southern part, increased markedly in recent years. These findings imply that the current mitigation strategy still has some insufficiencies, and to reduce the exposure risk in the future, China needs to set more ambitious mitigation targets and continue to push forward and strengthen the synergetic control of multiple air pollutants.